1996
DOI: 10.1074/jbc.271.47.29764
|View full text |Cite
|
Sign up to set email alerts
|

Role of Negatively Charged Residues in the Fifth and Sixth Transmembrane Domains of the Catalytic Subunit of Gastric H+,K+-ATPase

Abstract: The role of six negatively charged residues located in or around the fifth and sixth transmembrane domain of the catalytic subunit of gastric H ؉ ,K ؉ -ATPase, which are conserved in P-type ATPases, was investigated by site-directed mutagenesis of each of these residues. The acid residues were converted into their corresponding acid amides. Sf9 cells were used as the expression system using a baculovirus with coding sequences for the ␣-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
79
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 59 publications
6
79
4
Order By: Relevance
“…ATPase Activity of Various Subunit Combinations-In previous studies we showed that the activity of any ATPase overexpressed in Sf9 cells can be easily measured at low ATP concentrations in a membrane preparation of these cells because of the low endogenous ATPase activity under these conditions (43). When measured at 0.1 mM ATP, neither the ion-independent nor the K ϩ -dependent ATPase activity differed between membranes of mock-infected cells or cells expressing HK␣ 2 a alone (Fig.…”
Section: Subunit Expression In Sf9mentioning
confidence: 99%
“…ATPase Activity of Various Subunit Combinations-In previous studies we showed that the activity of any ATPase overexpressed in Sf9 cells can be easily measured at low ATP concentrations in a membrane preparation of these cells because of the low endogenous ATPase activity under these conditions (43). When measured at 0.1 mM ATP, neither the ion-independent nor the K ϩ -dependent ATPase activity differed between membranes of mock-infected cells or cells expressing HK␣ 2 a alone (Fig.…”
Section: Subunit Expression In Sf9mentioning
confidence: 99%
“…After expression in yeast, we found that these mutants had a low Ca 2ϩ -ATPase activity (32). It is noteworthy that in gastric H ϩ ,K ϩ -ATPase, residues Glu-837 and Asp-839, which correspond to Asp-813 and Asp-815 in Ca 2ϩ -ATPase, were found to render the ATPase unphosphorylatable by ATP when mutated to glutamine and asparagine residues, respectively (33).…”
mentioning
confidence: 99%
“…Recently, in H ϩ ,K ϩ -ATPase Swarts et al (27) have identified 3 new functionally important amino acid residues (Glu-834, Glu-837, and Glu-839) in the C-terminal part of the ␣ subunit. In most P-type ATPase alignments, these residues have been proposed to reside in a cytosolic loop (L6 -7), between the 6th and 7th transmembrane segment (Ref.…”
mentioning
confidence: 99%